Evaluación de un compuesto bioactivo altamente diluido para el control de Lasiodiplodia theobromae en plántulas de cacao (Theobroma cacao L.) - Troncozo Correa, Juan Bautista (2023)
Cocoa plays an important role in the economy and constitutes the main component of export products. It is affected by Lasiodiplodia theobromae, causing plant death. As a solution, highly diluted bioactive compounds (HDBC) influence the biological processes of plants, contributing to the MIP. The research was conducted at the Campus “La María” de la Universidad Técnica Estatal de Quevedo. With the objective of evaluating a highly diluted bioactive compound for the control of Lasiodiplodia theobromae in cocoa seedlings (Theobroma cacao L.). The treatments consisted of the application of three concentrations of CBD (1C, 6C and 12C) and two forms of application, edaphic and foliar plus a control for each application method. A completely randomized design (DCA) was used with an ADEVA and subsequent Tukey test at 95%. The variables evaluated were: severity, incidence, dead leaves, plant height, number of leaves, stem and root length, fresh leaf weight, root weight. The application methods provided a decrease in severity and incidence in the 1C dilution with 66.66% and 73.33% respectively, reducing the number of dead leaves. In addition, the condition of the plants improved, increasing agronomic variables such as plant height (39.17 cm), number of leaves (18 units), fresh leaf weight (10.20 grams), root length (32.63 cm), root weight (16.07 grams). The bioactive compound optimized the variables of severity and incidence, indicating that the use of HDBC favors the control of the pathogen without negative effects for the plant Keywords: Lasiodiplodia theobromae, agrohomeopathy, application methods, severity, agronomic variables.